Conditions of intensive evaporation of heterogeneous water droplet in high-temperature gaseous medium - O. V. Vysokomornaya; M. V. Piskunov; P. A. Strizhak (Известия высших учебных заведений: Проблемы энергетики)
The numerical simulation of heat and mass transfer processes at intensive evaporation of a heterogeneous water droplet (with a solid inclusion - carbon particle) in a high-temperature (more than 800 K) gaseous medium in conducted. The characteristic periods of water droplet heating up to the conditions of an intensive vaporization (reaching of the boiling temperature at the interface “solid inclusion - liquid”) are established. The influence of external gaseous medium temperature, the main properties of inclusion material on these periods is determined. The necessary and sufficient conditions of the intensive vaporization in the system “water droplet with a solid inclusion - high-temperature gases” are pointed out.